The Impact Of a Training Curriculum Using Spaces To Develop Football Offensive Plans - Mawlood, Dhiaa Hamood; Adulrazak, Zahid Sbhee; Saleh, Ahmed Selman (International Journal of Psychosocial Rehabilitation, 2020)
As a result of the development of football and branching requirements for the preparation of the team and players called the researchers to find plans to modernize the development of offensive play through the use of general plans implemented by a specific number of players and often take the area of the playground is smaller than that required to implement the basic plans and these plans to create and use vacant spaces. The researchers used the experimental approach to design a single group with tribal and remote standards in order to extract the percentage of development in the attacking football plans. The research sample includes (22) players of the advanced players of Al-Khalis football club participating in the first division qualifying to the excellent season for the season (2018-2019). The research community is the Diyala clubs of 7 clubs (Diyala, Khalis,al mokdadea, Shahraban, Habhb, Baldruz, New Shat). . Prepared by the researchers form and with the assistance of a number of specialists in the testing and measurement in order to know the possibility of players in the exploitation of empty spaces during the implementation of offensive play plans (creating empty spaces and exploitation of the ball, creating empty spaces and exploitation without a ball, the receipt and delivery of the ball in the void, , Time of the attack) in the team and the performance of the players was assessed by a group of arbitrators and specialists with football during the performance in the games. The researchers implemented the training curriculum after presenting it to a number of experts and specialists in the field of football. The syllabus was applied during the special preparation period and consists of (12) weeks with (5) training modules per week and 20 minutes of the daily training unit. The number of training units was (60) units. After applying the appropriate statistical means and through the results teams between the tribal and remote tests, the researcher noticed significant differences between the two tests and the benefit of the post-test in the tests under study